Impaired Corneal Biomechanical Properties and the Prevalence of Keratoconus in Mitral Valve Prolapse - Emine Kalkan Akcay; Murat Akcay; Betul Seher Uysal; Pinar Kosekahya; Abdullah Nabi Aslan; Mehtap Caglayan; Cemal Koseoglu; Fatma Yulek; Nurullah Cagil (Journal of Ophthalmology)
Objective. To investigate the biomechanical characteristics of the cornea in patients with mitral valve prolapse (MVP) and the prevalence of keratoconus (KC) in MVP. Materials and Methods. Fifty-two patients with MVP, 39 patients with KC, and 45 control individuals were recruited in this study. All the participants underwent ophthalmologic examination, corneal analysis with the Sirius system (CSO), and the corneal biomechanical evaluation with Reichert ocular response analyzer (ORA). Results. KC was found in six eyes of four patients (5.7%) and suspect KC in eight eyes of five patients (7.7%) in the MVP group. KC was found in one eye of one patient (1.1%) in the control group (P=0.035). A significant difference occurred in the mean CH and CRF between the MVP and control groups (P=0.006 and P=0.009, resp.). All corneal biomechanical and topographical parameters except IOPcc were significantly different between the KC-MVP groups (P<0.05). Conclusions. KC prevalence is higher than control individuals in MVP patients and the biomechanical properties of the cornea are altered in patients with MVP. These findings should be considered when the MVP patients are evaluated before refractive surgery.